2020
DOI: 10.1007/s00296-020-04602-8
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and patient-reported outcomes in patients with rheumatoid arthritis and Sjögren’s syndrome enrolled in a large observational US registry

Abstract: The objective of this study was to compare rheumatoid arthritis (RA) disease activity and patient-reported outcomes (PROs) in a national sample of patients with RA with/without Sjögren's syndrome (SS). Adults with RA from a large observational US registry (Corrona RA) with known SS status between 22 April 2010 and 31 July 2018 and a visit 12 (± 3) months after index date were identified (n = 36,256/52,757). SS status: determined from a yes/no variable reported at enrolment into the Corrona RA registry and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…The studies identified were remarkably similar: 49 of 65 reported on surgical interventions; of the remaining16; 3 studied alternative treatments 8,25,29 ; 4 studied epidemiological risk factors like obesity, 22 old age, 21 opioid abuse, 23 and smoking 43,59 ; only 4 studies investigated pharmacological interventions 28,67,71,81 ; the remaining studied patient-professional-interaction or behavioural medicine, 19,66 radiotherapy, 49 implants, 69 or compared 2 disease progressions under routine care. 26 Of the 49 studies on surgical interventions, 23 focussed on postsurgical pain, with 3 investigating chronic postsurgical pain. 11,65,80 Very few studies mentioned a study registration 13 or provided a link or identifier of a publicly accessible protocol in a central register.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies identified were remarkably similar: 49 of 65 reported on surgical interventions; of the remaining16; 3 studied alternative treatments 8,25,29 ; 4 studied epidemiological risk factors like obesity, 22 old age, 21 opioid abuse, 23 and smoking 43,59 ; only 4 studies investigated pharmacological interventions 28,67,71,81 ; the remaining studied patient-professional-interaction or behavioural medicine, 19,66 radiotherapy, 49 implants, 69 or compared 2 disease progressions under routine care. 26 Of the 49 studies on surgical interventions, 23 focussed on postsurgical pain, with 3 investigating chronic postsurgical pain. 11,65,80 Very few studies mentioned a study registration 13 or provided a link or identifier of a publicly accessible protocol in a central register.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, in this systematic search trying to identify real-word data and evidence studies, only 6 reports used the term “real-world data” in the full text, 26 , 28 , 29 , 71 , 79 , 87 only one used the term “real-world evidence”, 28 and only 2 studies used the term “real-world” in the title. 28 , 71 Despite no time filter in our search, most studies were conducted recently, with only one published in 2009, 66 7 in 2014 to 16, 31 in 2017 to 2019, and 26 since 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although KCS and sSS are not considered severe EAM [42], patients with both RA and sSS have an increased disease burden, decreased quality of life, are more likely to have a longer duration of RA, worse joint damage and lower reduction in RA disease activity at 12 months compared with patients with RA only [43][44][45]. The correlation of sSS with increased RA disease burden includes an association with higher RA disease activity and ACPA positivity, which indicates a poor prognosis [43,46].…”
Section: Keratoconjunctivitis Siccamentioning
confidence: 99%
“…There are no current guidelines recommendations for treating patients with both RA and sSS [45], and there is a paucity of studies on outcomes on RA-related KCS with systemic therapy. Hydroxychloroquines, corticosteroids, rituximab, anti-TNF agents, methotrexate and others showed to improve KCS features in SS.…”
Section: Corneal Complicationsmentioning
confidence: 99%